Employment of government accounting system using the government financial statistics system GFS in municipalities: Applied study in the municipality of Karbala and the municipalities of districts and sub districts - Asaad Mohammed Ali Awad; Huda Ahmed Ali Al-Mutairi (Iraqi Journal for Administrative Sciences, 2024)
The objective of this research is to employ Sustainability Accounting Standards (standard FNO101 by SASB Commercial Banks) by analyzing the content of annual report of commercial banks listed in Iraq Stock Exchange to understand the extent of commercial banks alliance of Sustainability reporting and to employ this standards for enhancing disclosure , transparency verifying. This research also aim to know the attitude of the employee of this banks about the important of Sustainability belong to FNO101 throw Questionnaire . The research show that commercial banks committee to Sustainability reporting by 51.54% as a mention for all banks this rate acceptance that over 50% and there are contrast for high rate 72.22% in 2016 of ( Altanmia International Bank ) that have best performance between other banks according to (CAMELS) scale that issued by Iraqi Central Bank in cooperation with AR nest & young company ,this is show that applying Standard FNO101 are good for measuring performance .The low rate of Sustainability reporting is 33.332% -2016 of (Erbil Investment and financing bank) .